2009
DOI: 10.1002/chir.20697
|View full text |Cite
|
Sign up to set email alerts
|

Chiral separations of some β‐adrenergic agonists and antagonists on AmyCoat column by HPLC

Abstract: Sixteen beta-adrenergic antagonists namely acebutalol, alprenolol, atenolol, bisoprolol, bopindolol, bufurolol, carazolol, celiprolol, indenolol, metaprolol, nebivolol, oxprenolol, practolol, propranolol, tertalol, and timolol, and two beta-adrenergic agonists namely cimeterol and clenbuterol were resolved on AmyCoat (150 x 46 mm, 3 microm size of silica particle) by using (85:15:0.1, v/v/v), (90:10:0.1, v/v/v), and (95:05:0.1, v/v/v) combinations of n-heptane, ethanol, and diethylamine solvents, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Therefore, it may be concluded that π‐π interactions are the major controlling forces in the chiral separation. This fact has already been published by our group . Briefly, the enantiomers of these drugs fitted stereospecifically in the chiral groove.…”
Section: Mechanism Of Separation At the Supramolecular Levelmentioning
confidence: 78%
“…Therefore, it may be concluded that π‐π interactions are the major controlling forces in the chiral separation. This fact has already been published by our group . Briefly, the enantiomers of these drugs fitted stereospecifically in the chiral groove.…”
Section: Mechanism Of Separation At the Supramolecular Levelmentioning
confidence: 78%
“…It is attractive to report that the reported profens have a benzene ring facilitating π–π interactions among the antipodes and chiral amylose derivatives. It is already established that π–π interactions are crucial in the chiral separation of many aromatic racemates . The setting of all the antipodes of profens in the derivatized amylose grooves is depicted in Figures .…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that the reported dipeptide is aromatic, providing π–π interactions with chiral selectors. It is prominent that π–π forces are stronger than others participating in chiral separation . Therefore, these forces are accountable for the best chiral separation of the stereomers.…”
Section: Resultsmentioning
confidence: 99%